Pengaruh Pemberian Ekstrak Kunyit (Curcuma domestica) Dalam Air Minum Terhadap Performa Produksi Ayam Ras Petelur Fase Layer - Irvan Fujiyanto; Oki Imanudin; Dini Widianingrum (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
This study aims to analyze the effect of giving turmeric extract as an additive in drinking water on the production performance of layer phase laying hens. The experimental design used in this study was a completely randomized design (CRD) carried out experimentally with 60 laying hens in the layer phase of the Isa Brown type with five treatments and four replications. The treatment used was P0 (without adding turmeric extract) as a control, P1 (1% turmeric extract), P2 (2% turmeric extract), P3 (3% turmeric extract), P4 (4% turmeric extract). The variables observed included Ration Consumption, Body Weight Growth (PBB), Feed Conversion Ratio (FCR), Drinking Water Consumption, Hen Day Production (HDP). The research data were analyzed using analysis of variance and if they showed significant differences then they were further tested using Duncan's multiple range test. The results showed that the addition of turmeric extract as an additive had a significant effect (P<0.05) on the production performance of layer phase laying hens (P<0.05) on Feed Conversion Ratio (FCR), Drinking Water Consumption and Hen Day production (HDP). For drinking water consumption, the highest yield was P0 = 7,132,50 ± 187,68a. At FCR the highest result was obtained P2 = 2,35 ± 0,26a, while at HDP the highest result was obtained P1 = 69,75 ± 11,58a. The conclusion from this study is that the addition of turmeric extract can be used as a feed additive to extend the shelf life of laying hens.